2003
DOI: 10.1093/bioinformatics/btg111
|View full text |Cite
|
Sign up to set email alerts
|

Do current sequence analysis algorithms disclose multifunctional (moonlighting) proteins?

Abstract: A number of multifunctional, 'moonlighting', proteins have been analyzed by different current programs to test whether they identify both functions. PSI-BLAST and PRODOM perform best in predicting the alternative function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 5 publications
1
36
0
Order By: Relevance
“…The difficulty in prediction is reflected by work done with known moonlighting proteins as a starting point to test different algorithms. Although domains for alternative functions were found by bioinformatic analysis, the predictive power appeared to be very low (57). The limitations currently associated with automated protein function prediction have been reviewed by Friedberg (52).…”
Section: Final Remarksmentioning
confidence: 99%
“…The difficulty in prediction is reflected by work done with known moonlighting proteins as a starting point to test different algorithms. Although domains for alternative functions were found by bioinformatic analysis, the predictive power appeared to be very low (57). The limitations currently associated with automated protein function prediction have been reviewed by Friedberg (52).…”
Section: Final Remarksmentioning
confidence: 99%
“…First, they rely heavily on the existence of functional annotation of a protein (Chapple et al, 2015;Pritykin et al, 2015), which is a major bottleneck of the problem. Second, all the existing methods address different aspects of MPs' functional diversity: sequence similarity (Gomez et al, 2003;Khan et al, 2012), motifs/ domains, structural disorder (Hern andez et al, 2011), or proteinprotein interaction (PPI) patterns combined with existing gene ontology (GO) annotations (Chapple et al, 2015;G omez et al, 2011;Pritykin et al, 2015). However, the diverse nature of MPs' functions, cellular locations, function switching mechanisms, and the organisms in which they are found gives compelling evidence that in order to understand and identify the overall functional aspects of these proteins, one should characterize these proteins in a wider functional/proteomic space.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional sequence-based functional annotation methods that are based on the concept of homology [21] or conserved motifs/domains [22][23][24] will have problems for identifying secondary functions because there are cases that a homolog of a moonlighting protein does not possess the secondary function [25] or has a different secondary function [16,26,27]. There are two studies that have investigated whether existing sequencebased function prediction methods can identify distinct dual functions of moonlighting proteins [28,29]. Gomez et al compared eleven methods and reported that PSI-BLAST [21] performed relatively well in identifying moonlighting functions [28].…”
Section: Introductionmentioning
confidence: 99%
“…There are two studies that have investigated whether existing sequencebased function prediction methods can identify distinct dual functions of moonlighting proteins [28,29]. Gomez et al compared eleven methods and reported that PSI-BLAST [21] performed relatively well in identifying moonlighting functions [28]. We have compared our function prediction tools, PFP [30,31] and ESG [32], with PSI-BLAST and showed that PFP, which mines function information from weakly similar sequences, had the best performance in predicting two distinct functions of moonlighting proteins [29].…”
Section: Introductionmentioning
confidence: 99%